LICENSING OF MANICURISTS IN THE UNITED STATES: BARRIERS AND OPPORTUNITIES FOR IMMIGRANTS AND LOW-INCOME CITIZENS - Boldyzheva, Anastasiia (European Journal of Interdisciplinary Issues, 2024)
Manicurist licensing in the US is a crucial topic due to its significant impact on the economic integration of immigrants and low-income citizens. The nail care industry serves as a key small business sector, providing employment for thousands of people, especially in densely populated states like California and New York. However, strict licensing requirements become barriers for many workers, limiting access to the legal labor market and fostering the development of the informal economy. The purpose of the study is to determine the impact of the manicurist licensing system in the US on the socio-economic status of immigrants and low-income citizens. The study employed both qualitative and quantitative approaches. An analysis of literary sources, official reports, and scientific publications on licensing practices in various US states was conducted. The socio-economic approach allowed an assessment of the impact of regulatory requirements on immigrants’ income and working conditions. The systemic approach provided a comprehensive analysis of the licensing system’s influence on the labor market and regional development. The study’s results indicate that the nail care industry serves as an important income source for immigrants and individuals with low educational levels. However, licensing creates significant barriers due to high financial costs, extensive training requirements, and mandatory language proficiency standards. In some states, the licensing process is further complicated by additional conditions such as proof of legal status. This leads to the expansion of the informal labor market, where workers earn lower wages and lack social protections. Manicurist licensing in the US requires significant reforms to ensure equal access to the professional market. Reducing regulatory barriers, eliminating language requirements, shortening training hours, and lowering fees would promote greater employment opportunities for immigrants. Improving conditions in this sector is possible through state-supported programs and social initiatives that stimulate small business development and economic integration.